(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Primary aim of the paper is to generate the quality of power from the renewable energy resource, the wind system is considered here. In general the system is operated in two mode conditions i. standalone mode ii. Grid connected mode. This paper explains the control of a standalone system using two different control schemes namely a. generator side control scheme b. load side control scheme. Which are helps to regulate output voltage levels and power delivered to load with any disturbances even in the variations caused in the input side, The MATLAB platform is used for the testing control strategy. The purpose of control is to adjust the inverter voltage’s amplitude and frequency at a variable speed of the wind. This article presents a Generalized Predictive Control application to a wind power converting system with emphasis on the Maximum Power Point Tracking (MPPT). The controller developed consists RST regulator obtained GPC.